IMPACTO NA QUALIDADE DOS SERVIÇOS PRESTADOS, AOS PACIENTES INTERNADO PELO SISTEMA ÚNICO DE SAÚDE, NO SETOR DE ONCOLOGIA, APÓS PROGRAMA DE TREINAMENTO COM A ENFERMAGEM. - STEFANELI, ROUSE CRISTINA; CAVALARI, NILTON (Brazilian Journal of Surgery & Clinical Research)
The present work it is a diagnosis of the quality of nursing services provided to cancer patients hospitalized at Health System, in a large general hospital in the northern region of Paraná. Presents the age profile and education for professionals involved in the care of cancer patients. Highlights the need for specific training for nursing professionals. Points out areas where, in this case, there is a greater need for training. It analyzes the results obtained through field research before and after the training sessions.